2016
DOI: 10.1002/adsc.201500936
|View full text |Cite
|
Sign up to set email alerts
|

CH Functionalization/CO Bond Cleavage of Benzyl Silyl Ethers with Ynamides for the Chemoselective Synthesis of Skeletally Diverse Compounds

Abstract: Described here is ap ractical carbocationinitiated formal [3 + + 2] or [4 + + 2] cycloaddition reaction for the diversity-oriented syntheses of 1-amidoindenes and 2-amido-4H-chromenes.T he Lewis acid-promoted annulation of ynamides andb enzyl silyl ethers efficiently constructs1 -amidoindenes via C À Hf unctionalization of benzyls ilyl ethers.B yu tilization of o-methoxybenzyl silyl ethers,2 -amido-4H-chromenes are also constructed via C À Ob ond cleavage of benzyl silyl ethers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Reaction of ynamide 124 with benzyl silyl ethers 217 activated by zinc bromide was shown to promote a formal cationic [2+3] cycloaddition to give 1-amino-3H-indenes 219 through keteniminium ions 128 (Scheme 40). 126 In contrast, the presence of an additional methoxy group in 221 provided 2-aminochromenes 222 from a formal [2+4] cycloaddition, 126 a reaction that was also shown to proceed starting from 2-methoxyaroyl chorides, 127a oxetanes, and aziridines. 127b From a similar perspective, a modular synthesis of 4-aminoquinolines 225, an especially relevant scaffold for the design of antimalarial drugs, was recently reported by the Bräse group.…”
Section: Review Syn Thesismentioning
confidence: 99%
“…Reaction of ynamide 124 with benzyl silyl ethers 217 activated by zinc bromide was shown to promote a formal cationic [2+3] cycloaddition to give 1-amino-3H-indenes 219 through keteniminium ions 128 (Scheme 40). 126 In contrast, the presence of an additional methoxy group in 221 provided 2-aminochromenes 222 from a formal [2+4] cycloaddition, 126 a reaction that was also shown to proceed starting from 2-methoxyaroyl chorides, 127a oxetanes, and aziridines. 127b From a similar perspective, a modular synthesis of 4-aminoquinolines 225, an especially relevant scaffold for the design of antimalarial drugs, was recently reported by the Bräse group.…”
Section: Review Syn Thesismentioning
confidence: 99%
“…Following general procedure 5, the product was purified by column chromatography on silica gel (eluent: petroleum ether/ethyl acetate = 2/1 to petroleum ether/ethyl acetate = 1/1) to afford the desired product 3m; yellow liquid; yield: 95% (63.1 mg); 1 H NMR (400 MHz, CDCl 3 ): δ 8.01 −8.03 (m, 2H), 7.31−7.17 (m, 7H), 7.14−7.03 (m, 4H), 3.88 (s, 2H), 1.37 (s, 9H); 13 C{ 1 H} NMR (100 MHz, CDCl 3 ): δ 156. 8,152.9,143.8,142.1,140.2,136.8,128.7,128.6,127.9,127.0,126.0,124.7,124.7,123.9,121.4,117.0,82.1,30.7,28.1;HRMS (ESI) O 3 , 345.1234;found, 345.1231. 3-(6-Nitro-3-phenyl-4H-chromen-2-yl)oxazolidin-2-one (3n).…”
Section: -M E T H Y L -N -P H E N Y L -N -( T H I O P H E N -3 -Y L E...mentioning
confidence: 99%
“…7 Recently, some elegant methods have been reported for the synthesis of 2-amino-4H-chromenes via cycloaddition of ynamides. For example, in 2016, Cao and his co-workers 8 developed ZnBr 2 -promoted formal [4+2] annulation of ynamides with o-methoxybenzyl silyl ethers to construct this framework (Scheme 1a). However, this method suffered from certain salient drawbacks, for example, low yields (41−65%), narrow substrate scopes, and 1.2 equiv Lewis acid ZnBr 2 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…In 2017, Zhao and Gagosz published a gold-catalyzed hydride shift towards the synthesis of N -allenyl amides/azoles from N -alkynyl amides/azoles (Scheme 76) [120]. Under optimized conditions, the researchers found that a large number of N -alkynyl amides and azoles were tolerated in this reaction ( 282a – d ): N -alkynyl indole, pyrrole, and carbazole all gave the respective allene products ( 283a – d ), additionally a variety of R 1 and R 2 substitutions were tolerated.…”
Section: Reactions Of N-alkynyl Azolesmentioning
confidence: 99%